DIFFERENCES IN INCREASING VO2 MAX BETWEEN BRISK WALKING AND HIGH INTENSITY INTERVAL TRAINING (HIIT) IN YOUNG ADULTS - Cindy Calista Chandra; Yosef Purwoko; Sumardi Widodo; Tanjung Ayu Sumekar (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2019)
Background: Sedentary lifestyle is widely adopted by the society. Sedentary lifestyle is associated with limited physical activity, thereby increasing the risk of diseases, as well as reducing fitness. Fitness is assessed with VO2Max. However, people with sedentary lifestyle are reluctant to exercise, thus the authors want to see whether briskwalking, an easy exercise and HIIT, a short-time exercise can increase VO2Max. Research Method: Quasi-experimental research with a pre-test and post-test comparison group design. 60 young adult women were divided into three groups, namely brisk walking, HIIT, and control by using purposive sampling. The brisk walking group did brisk walking and HIIT did HIIT aerobics for six weeks, three times in every week. The control group was not treated. All subjects performed VO2Max pretest and posttest with Cooper test. Result: The VO2Max value for brisk walking and HIIT increased by averages of 9.83±3.93 and 8.84±4.76, while the control decreased by -3.97±4.02 The result from paired t-test and Wilcoxon shows significancy thus indicating a significant difference of VO2 max value before and after the treatments towards the brisk walking, HIIT, and control groups. After the Mann Whitney test is performed, no significant difference is found between brisk walking and HIIT, whereas there is a significant difference between brisk walking and control, and also between HIIT and control. Conclusion: Brisk walking and HIIT can increase VO2Max. However, there was no difference in the increase between brisk walking and HIIT.Key Words: VO2Max, brisk walking, HIIT